Selection of prey to improve biological parameters of the predator Podisus nigrispinus (Dallas, 1851) (Hemiptera: Pentatomidae) in laboratory conditions - Bortoli,S. A. De (2016)
Abstract Mass production of predatory stinkbugs in the laboratory is prioritized to release them into the field as part of IPM programs. Therefore, the aim of this study was to identify the best prey for rearing the predator Podisus nigrispinus (Dallas, 1851) (Hemiptera: Pentatomidae) among five different species of insect (three of Lepidoptera, one of Coleoptera, and one of Diptera). Second-instar P. nigrispinus nymphs were conditioned in transparent 1000-mL plastic pots, adults were placed in Petri dishes for mating, and both stages were maintained under controlled conditions (25 ± 1°C, 12 hours of photophase, 70 ± 10% RH). Nymphs and adults of P. nigrispinus consumed more Musca domestica (Linnaeus, 1758) (Diptera: Muscidae) larvae than the other tested prey. The consumption of fly larvae was 1.5 larvae/day/nymph and adults 1.7 larvae/day/adult. However, the number of eggs per female was less when the predator consumed M. domestica larvae (407.8 eggs/female) and most when consumed the Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) larvae (797.7 eggs/female). Furthermore, the percentage of hatched eggs was greater when the predator females consumed D. saccharalis larvae (90.0%). D. saccharalis larvae is the best prey to rearing P. nigrispinus.